American cultural studies - Campbell, Neil (Routledge, 2015)
New beginnings: American culture and identity -- Ethnicity and immigration: between many worlds -- African Americans: "I don't sing other people's voices" -- In God we trust?: religion in American life -- Approaches to regionalism: the west and the south -- The American city: "the old knot of contrariety" -- Gender and sexuality: "to break the old circuits" -- Representing youth: outside the sunken nursery -- The spread of freedom -- The transmission of American culture.; Includes bibliographical references and index